Shuffling of Genes Within Low-Copy Repeats on 22q11 (LCR22) by Alu-Mediated Recombination Events During Evolution - Babcock, Melanie; Pavlicek, Adam; Spiteri, Elizabeth; Kashork, Catherine D.; Ioshikhes, Ilya; Shaffer, Lisa G.; Jurka, Jerzy; Morrow, Bernice E.

(untitled) (Genome Research, 2003)
Low-copy repeats, or segmental duplications, are highly dynamic regions in the genome. The low-copy repeats on chromosome 22q11.2 (LCR22) are a complex mosaic of genes and pseudogenes formed by duplication processes; they mediate chromosome rearrangements associated with velo-cardio-facial syndrome/DiGeorge syndrome, der(22) syndrome, and cat-eye syndrome. The ability to trace the substrates and products of recombination events provides a unique opportunity to identify the mechanisms responsible for shaping LCR22s. We examined the genomic sequence of known LCR22 genes and their duplicated derivatives. We found Alu (SINE) elements at the breakpoints in the substrates and at the junctions in the truncated products of recombination for USP18, GGT, and GGTLA, consistent with Alu-mediated unequal crossing-over events. In addition, we were able to trace a likely interchromosomal Alu-mediated fusion between IGSF3 on 1p13.1 and GGT on 22q11.2. Breakpoints occurred inside Alu elements as well as in the 5′ or 3′ ends of them. A possible stimulus for the 5′ or 3′ terminal rearrangements may be the high sequence similarities between different Alu elements, combined with a potential recombinogenic role of retrotransposon target-site duplications flanking the Alu element, containing potentially kinkable DNA sites. Such sites may represent focal points for recombination. Thus, genome shuffling by Alu-mediated rearrangements has contributed to genome architecture during primate evolution.